OVERCOMING LISTENING CHALLENGES WITH AUTHENTIC MATERIALS IN EFL EDUCATION (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the various challenges faced by EFL learners in developing their listening skills and discusses how the use of authentic materials can help address these challenges. By exposing learners to a variety of spoken English in real-world contexts, authentic materials enhance comprehension, build listening strategies, and prepare learners for practical language use. The paper concludes by highlighting strategies for effectively integrating authentic materials into EFL classrooms to maximize listening development.